PEMANFAATAN BIJI JALI SEBAGAI INOVASI PANGAN LOKAL MELALUI PEMBUATAN BROWNIES JALI DI DESA SUKOREJO - Isnandar Slamet; Aditya Agung Nugroho; Annisa Aulia Rahma; Dafa Amalia Hanifah; Della Novita Sari; Faizah Zata Ismah Indriyanto; Futri Rahmadini; Nathania Kintan Maharani; Rosika Alifah Anjani; Septina Anggraini; et al. (JURNAL PENGABDIAN MANDIRI, 2025)
The utilization of local food resources is an essential effort to support diversification and food security. Job’s tears (Coix lacryma-jobi L.) contain high nutritional value and can be processed into modern food products with economic potential, such as jali brownies. This training program was conducted in Sukorejo Village, Sambirejo District, Sragen Regency, involving housewives from Plalangan Hamlet. The method included socialization on the nutritional and economic potential of Job’s tears, followed by a direct demonstration of making brownies using jali flour. The results showed an improvement in participants’ knowledge and skills in processing jali into healthy, appealing, and marketable food products. Overall, this activity demonstrated that the innovation of jali brownies not only promotes the use of local food but also contributes to economic empowerment within rural communities